2019
DOI: 10.1002/poc.3968
|View full text |Cite
|
Sign up to set email alerts
|

4‐(4‐Bromophenyl)thiazol‐2‐amine: Crystal structure determination, DFT calculations, visualizing intermolecular interactions using Hirshfeld surface analysis, and DNA binding studies

Abstract: 2-Aminothiazole is a valuable synthon in organic synthesis and an important structural unit of pharmaceutically active drugs. It is accessible via several synthetic routes. In the current account, compound 4 {4-(4-bromophenyl) thiazol-2-amine} was synthesized by employing a recently reported procedure of Gabriel synthesis using Lawesson reagent. The title compound was characterized through spectro-elemental analytical data, and its crystal structure was determined by single-crystal X-ray diffraction. The torsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The energy gap between LUMO and HOMO determine the electronic structure that could further lead to predict the kinetic stability and reactivity of a compound. 42 The compound (4) was detected to be unstable one because of the small energy gap (Δ E ) value; hence could be inferred as reactive in nature, Table 3 . The small value of hardness ( η ), while a greater value of softness ( S ) further indicated the polarizable nature of the compound (4), as also obvious from computed polarizability and dipole moment values and validated its instability that is necessary for its binding interactions with protein/or DNA molecule, Table 3 ,.…”
Section: Resultsmentioning
confidence: 99%
“…The energy gap between LUMO and HOMO determine the electronic structure that could further lead to predict the kinetic stability and reactivity of a compound. 42 The compound (4) was detected to be unstable one because of the small energy gap (Δ E ) value; hence could be inferred as reactive in nature, Table 3 . The small value of hardness ( η ), while a greater value of softness ( S ) further indicated the polarizable nature of the compound (4), as also obvious from computed polarizability and dipole moment values and validated its instability that is necessary for its binding interactions with protein/or DNA molecule, Table 3 ,.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19,46 ] The spectral changes indicated that compound 3 intercalated via partial/or complete insertion into DNA base pairs. [ 17,47 ] Intercalation feasibility could be accredited to planarity in the compound's structure and related to the overlapping of intercalating chromophore's electronic state (π * antibonding orbitals) and stacked DNA base pairs (π bonding orbitals). This overlapping causes π ‐ π * coupling that decreases transition probability hence resulted in hypochromism in the compound's spectra after the addition of DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 10 shows the optimized structures of cationic porphyrin ligand ([L] 3+ ) and complexes ([Cu‐P1] 3+ , [Cu‐P2] 3+ , and [Cu‐P3] 3+ ), and then, their energy gap (Δ E ) (the difference between highest occupied molecular orbital [HOMO] and lowest unoccupied molecular orbital [LUMO]) are discussed in details; it plays important roles in determining electronic structures and the analysis of chemical reactions. [ 76–78 ] The frontier molecular orbital structures and calculated HOMO–LUMO energy gap (Δ E ) of cationic porphyrin ligand and complexes are described in Figures 11 and S16. The HOMO of ligand [L] 3+ was placed on Schiff base moiety, and LUMO was on the porphyrin ring.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 10 shows the optimized structures of cationic porphyrin ligand ([L] 3+ ) and complexes ([Cu-P1] 3+ , [Cu-P2] 3+ , and [Cu-P3] 3+ ), and then, their energy gap (ΔE) (the difference between highest occupied molecular orbital [HOMO] and lowest unoccupied molecular orbital [LUMO]) are discussed in details; it plays important roles in determining electronic structures and the analysis of chemical reactions. [76][77][78] The frontier molecular orbital structures and calculated HOMO-LUMO energy gap (ΔE) of cationic porphyrin ligand and complexes are described in Figures 11 and S16 surrounding of the metal center, but HOMO mainly localized at porphyrin complexes and LUMO at Schiff base complexes. Calculated HOMO-LUMO energy gap (ΔE) of complexes (0.33, 0.38, and 0.36 eV) was lower than free ligands (1.20 eV); these are attributed to after complexation of Cu 2+ , and there is a disruption of internal charge transfer that leads to changes in electronic properties.…”
Section: Dft Calculation Analysismentioning
confidence: 99%